Sorting and Long-Run Inequality - Fernandez, R.; Rogerson, R. (Quarterly Journal of Economics, 2001)
Many social commentators have raised concerns over the possibility that increased sorting in society may lead to greater inequality. To investigate this, we construct a dynamic model of intergenerational education acquisition, fertility, and marital sorting and parameterize the steady state to match several basic empirical findings. We find that increased sorting will significantly increase income inequality. Four factors are important to our findings: a negative correlation between fertility and education, a decreasing marginal effect of parental education on children's years of education, wages that are sensitive to the relative supply of skilled workers, and borrowing constraints that affect educational attainment for some low-income households.